Signal transduction by a nondissociable heterotrimeric yeast G protein - Klein, Shoshana (The National Academy of Sciences, 2000)
Many signal transduction pathways involve heterotrimeric G proteins. The accepted model for activation of heterotrimeric G proteins states that the protein dissociates to the free G(α) (GTP)-bound subunit and free G(βγ) dimer. On GTP hydrolysis, G(α) (GDP) then reassociates with G(βγ) [Gilman, A. G. (1987) Annu. Rev. Biochem. 56, 615–649]. We reexamined this hypothesis, by using the mating G protein of the yeast Saccharomyces cerevisiae encoded by the genes GPA1, STE4, and STE18. In the absence of mating pheromone, the G(α) (Gpa1) subunit represses the mating pathway. On activation by binding of pheromone to a serpentine receptor, the G(βγ) (Ste4, Ste18) dimer transmits the signal to a mitogen-activated protein kinase cascade, leading to gene activation, arrest in the G(1) stage of the cell cycle, production of shmoos (mating projections), and cell fusion. We found that a Ste4-Gpa1 fusion protein transmitted the pheromone signal and activated the mating pathway as effectively as when Ste4 (G(β)) and Gpa1 (G(α)) were coexpressed as separate proteins. Hence, dissociation of this G protein is not required for its activation. Rather, a conformational change in the heterotrimeric complex is likely to be involved in signal transduction.